2003
DOI: 10.1186/1471-2407-3-30
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor Trichostatin A modulates CD4+ T cell responses

Abstract: Background: Histone deacetylase inhibitors (HDACIs) induce hyperacetylation of core histones modulating chromatin structure and affecting gene expression. These compounds are also able to induce growth arrest, cell differentiation, and apoptotic cell death of tumor cells in vitro as well as in vivo. Even though several genes modulated by HDAC inhibition have been identified, those genes clearly responsible for the biological effects of these drugs have remained elusive. We investigated the pharmacological effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 66 publications
8
94
1
Order By: Relevance
“…It is likely that SAHA inhibits the transcription and translation of IL-2 in T cells and subsequently inhibits cytokine secretion by T cells and other cells such as macrophages. It was reported that an HDAC inhibitor (trichostatin A) represses IL-2 gene expression in anti-CD3 activated T cells (22). Low-dose SAHA treatment resulted in increased acetylation of histone H3 and decreased mRNA levels of IFN-␥ and TNF-␣ in activated spleen cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that SAHA inhibits the transcription and translation of IL-2 in T cells and subsequently inhibits cytokine secretion by T cells and other cells such as macrophages. It was reported that an HDAC inhibitor (trichostatin A) represses IL-2 gene expression in anti-CD3 activated T cells (22). Low-dose SAHA treatment resulted in increased acetylation of histone H3 and decreased mRNA levels of IFN-␥ and TNF-␣ in activated spleen cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…22 As such, HDAC inhibitors (HDACis) are now under intensive study for their feasibility as potential anti-rejection agents. 23,24 Suberoylanilide hydroxamic acid (SAHA), an FDAapproved drug for the treatment of cutaneous T-cell lymphoma, 25 is an HDACi composed of hydroxamic acid compound that can be well tolerated by the cancer patients. 26,27 While its role in anti-cancer therapy has been extensively studies, its impact on transplant rejection is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal agent TSA is another well-established HDACI also with potent antitumor activity (76)(77)(78). We examined whether the SDL interaction between RPD3 LOF and the overexpression of yTDP1 can be recapitulated using VPA and TSA.…”
Section: Rms Lines Expressingmentioning
confidence: 99%